Epidemiological changes in mumps infections between 1990 and 2017 in urban area of Shanghai, China - Pang, Hong; Zhou, Yibiao; Zhao, Wensui; Jiang, Qingwu (Human vaccines & immunotherapeutics, 2021)
2-dose measles-mumps-rubella (MMR) vaccine was recommended for children in Shanghai in November 1996 and incorporated into Shanghai immunization program in December 2008. We described the mumps epidemiology and assessed impact of the 2-dose MMR vaccination in Changning district, Shanghai, 1990-2017. We obtained the MMR vaccination coverage for children born during 1995-2015 and examined the incidence and disease characteristics of mumps during 1990-2017. The 1st dose MMR coverage had maintained above 95% since 1999 birth cohort. The 2nd dose MMR coverage reached above 90% since 2006 birth cohort. A total of 13,388 cases were reported during 1990-2017. The incidence decreased from 315.2 per 100,000 population in 1990 to 8.8 per 100,000 population in 2017. Of the 13,388 cases, 7585 (56.7%) were male and 91.7% were 1-14 years of age and 86.8% were children in kindergartens and students in schools. Compared with 1990-1996, the incidence had a significant decrease in 0-4 and ≥15 years in 1997-2008 and in all age groups in 2009-2017. A later birth cohort was associated with a lower incidence in children covered by MMR vaccination. In Conclusions, the incidence of mumps has dramatically declined with high coverage of 2-dose MMR in Changning district, Shanghai. Children in kindergartens and schools are still the most affected populations. An increase in incidence in adults has not occurred after 20 years of MMR vaccination. Long-term surveillance is needed to fully evaluate the impact of MMR vaccination policy.